Inter-carrier interference cancellation using spatial characteristics for high-mobility OFDM communication systems - Wei WANG; Qin-ye YIN; Peng-cheng MU (Tongxin xuebao)
High-mobility orthogonal frequency division multiplexing(OFDM)systems suffered severe inter-carrier interference(ICI)from Doppler spreading.On the basis of the characteristics of wireless propagation in practical scenarios,a method which employed the WINNER Ⅱ channel model to represent the practical wireless channel and an antenna array as the receiver to eliminate ICI in space-domain was proposed.The direction of arrival estimation algorithm and the beamforming network were used to separate the received signals in space-domain.Multi-beam diversity gain was obtained finally by means of combining the signals which have been compensated for Doppler frequency shifts(DFS)respectively.Simulation results demonstrate that the proposed method not only effectively reduces ICI and the error floors,but also obtains a 5～7 dB signal-to-interference gain over systems without use of the proposed method.